Improving cardiac myocytes performance by carbon nanotubes platforms† - Martinelli, Valentina; Cellot, Giada; Fabbro, Alessandra; Bosi, Susanna; Mestroni, Luisa; Ballerini, Laura (Frontiers in Physiology, 2013)
The application of nanotechnology to the cardiovascular system has increasingly caught scientists’ attention as a potentially powerful tool for the development of new generation devices able to interface, repair or boost the performance of cardiac tissue. Carbon nanotubes (CNTs) are considered as promising materials for nanomedicine applications in general and have been recently tested towards excitable cell growth. CNTs are cylindrically shaped structures made up of rolled-up graphene sheets, with unique electrical, thermal and mechanical properties, able to effectively conducting electrical current in electrochemical interfaces. CNTs-based scaffolds have been recently found to support the in vitro growth of cardiac cells: in particular, their ability to improve cardiomyocytes proliferation, maturation and electrical behavior are making CNTs extremely attractive for the development and exploitation of interfaces able to impact on cardiac cells physiology and function.